Comparison of opioid-limiting anesthesia methods in patients undergoing total abdominal hysterectomy - Osadcha , V.V.; Kobeliatsky, Yu.Yu. (Medicni Perspektivi, 2025)
The article reviews the comparison of opioid-limiting anesthesia methods in patients undergoing total abdominal hysterectomy. The aim of the study was to improve the method of anesthesia in the early postoperative period by reducing the dose of opioids, using 100 μg of morphine intrathecally. The quality of the perioperative period was analyzed in terms of inflammation, analgesia and comfort of women. Patients were randomly divided into 4 groups with different anesthesia methods: group I: endotracheal anesthesia – 25 women; group II: endotracheal anesthesia + epidural analgesia – 28 women; group III: endotracheal anesthesia + intrathecal morphine – 19 women; group IV: endotracheal anesthesia + intrathecal morphine + epidural anesthesia – 19 women. The following results were obtained: Leukocytes after surgery: (17.32 [14.48; 20.11]), (13.65 [11.27; 15.72]), (15.4 [13.4; 18.47]), (15.36 [13.47; 18.4]), which is significantly lower in group II, pI-IV =0.037. The next day: a statistically significant difference is observed between groups I and II-IV, pI-IV =0.047; after 3 days – no significant difference between the groups was detected, pI-IV >0.05. Patients of the first group required intramuscular morphine in 56% of cases, while patients of the second group – 21.4%, patients of the third group – 15.7%, and in the fourth group 0% – a significant difference (pI-IV =0.004). The pain index (M±m) on the visual analog scale after awakening (3.9±0.2); (1.4±0.3), (3.2±0.2); (0.7±0.1) – lower in the second and, especially, the fourth group pI-IV =0.001; after 3 hours – lower in the second and fourth groups, pI-IV =0.01; after 6 – lower in the third and fourth groups, pI-IV = 0.029; further, a statistical difference is observed in the decrease in the scores on the visual analog scale in the third and fourth groups. The time of the first need for analgesia (M±m) in group I was 1.8±0.2 hours, while in group II it was 2.8±0.2 hours, in group 3 it was 2.0±0.2 hours, while in group 4 it was 5.7±0.3 hours, which significantly prolongs the time of the first need for analgesia for group IV, p=0.0001. Therefore, after analyzing the data, we can conclude that the combination of intrathecal morphine and epidural analgesia is optimal for providing effective anesthesia.